Why do Asnaf Entrepreneurs Become Successful? The Role of Intention, Opportunity, and Resources - Efri Syamsul Bahri; Juhary Ali; Mohd Mizan Mohammad Aslam (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
Qardhawi's opinion on the 2009 zakah disbursement model related to the empowerment of productive aṣnāf has encouraged the development of productive zakah in poverty alleviation. This study aims to examine the effect of intentions, opportunities, and resources on successful aṣnāf entrepreneurs. The method used is the mono method, namely quantitative research. Data was obtained through a survey using purposive sampling. Primary data were examined using the PLS-SEM method and the SmartPLS application. This study found that the intention and opportunity factors had a positive and significant effect on the success of aṣnāf entrepreneurs. Meanwhile, resources have a negative impact on the success of aṣnāf entrepreneurs. This is evidence that the zakah resources given to aṣnāf entrepreneurs must be optimized so that they can have a significant impact. This finding provides recommendations to zakah management entities and policy makers to be able to increase the contribution of zakah funds in poverty alleviation through the aṣnāf entrepreneurial program.  AbstrakPendapat Qardhawi tentang model pencairan zakat tahun 2009 terkait pemberdayaan aṣnāf produktif telah mendorong berkembangnya zakat produktif dalam pengentasan kemiskinan. Penelitian ini bertujuan menguji pengaruh niat, peluang, dan sumber daya terhadap pengusaha aṣnāf yang sukses. Metode yang digunakan ialah metode mono yaitu penelitian kuantitatif. Data diperoleh melalui survei dengan menggunakan purposive sampling. Data primer diperiksa menggunakan metode PLS-SEM dan aplikasi SmartPLS. Penelitian ini menemukan bahwa faktor niat dan peluang berpengaruh positif dan signifikan terhadap keberhasilan wirausaha aṣnāf. Sementara itu, sumber daya berdampak negatif terhadap keberhasilan pengusaha aṣnāf. Hal ini menjadi bukti bahwa sumber daya zakat yang diberikan kepada pengusaha aṣnāf harus dioptimalkan agar mampu memberikan pengaruh signifikan. Temuan ini memberikan rekomendasi kepada entitas pengelola zakat dan pengambil kebijakan agar mampu meningkatkan kontribusi dana zakat dalam pengentasan kemiskinan melalui program wirausaha aṣnāf.